Composição nutricional, qualidade proteica, bioacessibilidade e biodisponibilidade de cálcio de linhaças germinadas marrom e dourada (Linum usitatissimum L.) - Pimenta, Alexandre Vinco (2019)
Seed germination promotes changes in its composition, providing potential health and nutritional benefits compared to non-germinated seeds. The aim of the present study was to verify the influence of germination on physicochemical characteristics, protein quality, bioaccessibility and bioavailability of brown and golden flaxseed (Linum usitatissimum L.) flaxseed by in vitro and in vivo studies. Flaxseed germination, brown and golden varieties, was performed for 48 hours at 26 ± 2° C. Afterwards, the flour of germinated and non-germinated flaxseed varieties was prepared and analyzed for centesimal composition, calcium determination, oxalate, phytate and tannin. In the in vitro study, the flours were subjected to an enzyme-simulated gastrointestinal digestion process to assess calcium bioaccessibility. For the in vivo calcium bioavailability study, 40 male Wistar rats were divided into five groups: Control (CT), Golden Flaxseed (LD), Brown Flaxseed (LM), Germinated Golden Flaxseed (LDG) and Germinated Brown Flaxseed (LMG). The study took place for six weeks and calcium balance was performed at six weeks to assess its bioavailability. At the end of the experimental time, the animals were euthanized, and blood samples were collected for biochemical analysis and femoral bone tissue for calcium analysis. For the in vivo protein quality study, 48 male Wistar rats were divided into six groups: without protein (AP), CT, LD, LM, LDG and LMG. The study took place during two weeks, being performed nitrogen balance in the second week to evaluate the protein quality. Statistical analysis was performed using the “two-way” analysis of variance (ANOVA) for the physicochemical characterization data, antinutritional factors and in vitro study of calcium bioaccessibility, in case of interaction the Tukey test was applied. In vivo studies were analyzed using “one-way” ANOVA, followed by Tukey test. Results were presented as mean ± standard deviation, being used p ≤ 0.05. Germination increased lipid and protein content and reduced carbohydrate content of flaxseeds. Calcium concentration is higher in the golden variety than in the brown one. The tannin content did not present statistical difference between the groups, while the phytate and oxalate contents showed significant reduction after germination. The germination promoted reduction of the phytate:calcium and oxalate:calcium molar ratio, being that in brown flaxseed these relations were superior to the golden variety. In the in vitro study, germinated flaxseeds showed a statistically higher percentage of bioaccessible calcium than their nongerminated samples. Also, calcium bioavailability was influenced by variety, being higher in golden flaxseed. Regarding the in vivo study, it was found that food intake, caloric intake, calcium intake, food efficiency ratio and caloric efficiency ratio; as well as weekly weight and total weight gain were similar for all groups. No differences were observed in intake, excretion (urinary and fecal) and calcium retention. Germination did not influence the calcium balance, but the germinated brown flaxseed was inferior to the control group. No statistical differences were observed in plasma calcium, phosphorus, creatinine and alkaline phosphatase levels. The present study did not show changes in the morphology and calcium content of the femurs of the animals. The Protein Efficiency Coefficient (PER) values did not differ between groups. However, germination promoted a reduction in Net Protein Efficiency Ratio (NPR) and relative PER and NPR, whereas for True Digestibility (DV), only brown flaxseed improved digestibility after germination. In conclusion, flaxseed germination promoted an increase in lipid and protein content, as well as a reduction in phytate and oxalate levels. The in vitro study showed that germination increased calcium bioaccessibility, while the in vivo study did not influence calcium bioavailability, although it had a negative effect on protein quality. The use of germinated flaxseed, regardless of variety, can contribute to increase the nutritional value of the diet without impairing calcium homeostasi